The Effectiveness of Project-Based Learning Model and Talking stickType of Cooperative Learning Model on the Quran-Hadith Subject Learning Outcomes - Ulya, Farchatin; Rifai RC, Achmad; Sulistyorini, Sri (Innovative Journal of Curriculum and Educational Technology, 2020)
In the Quran-Hadith learning activities, teachers still make use of conventional methods so that students do not achieve optimal results. Therefore, teachers, as managers in a learning process, are required to be creative in order to make their students learn more actively. This study aims to analyze the differences in learning outcomes gained by students treated using project-based learning model and talking sticktype of cooperative learning model withlevels of abilityand interaction as moderating variables. This study used a quantitative method throughan experimental approach using 2x2 factorial design. The results found there are differences in students’ learning outcomes using project-based learning model and talking sticktype of cooperative learning model with a significance value of 0,000; there were differences in learning outcomes between students with high ability and those with low ability with a significancevalue of 0.002; an interaction between the learning models and the students’ ability levels on their learning outcomes with a significance value of 0.011. The implication of this study is to provide teachers with direct experiences in examining the learning models and it can be used by teachers in selecting the proper learning model in improving the learning activity process.